Pengembangan Off Job Training Spesialis Perbaikan Boom Excavator Dengan Pengelasan GMAW Di PT Thiess - Galih Chandra Pratama; Wagiran Wagiran; Soeprapto Rachmad Said (Department of Mechanical Engineering Education, 2016)
The purpose of this study was to determine the characteristics and effectiveness of off-the-job training for repairing damaged boom excavator with GMAW welding processes in XXI Welder group at PT. Thiess. The research methods being used were Research and Development. Data were collected using observation, interview, test and questionnaire. The object of this study is class group, which is the apprentice group XXI Welder at PT. Thiess with 10 trainees as respondents. Data were analyzed using comparative statistics techniques with a non-parametric test. Data were compared based on the results obtained from the research instruments. The result shows the characteristics of learning off-the-job training, which are: learning is done based on case studies found in the workplace; the training participants is limited; the learning methods is group teaching, in which the learners are active with simulation methods. The effectiveness of learning off-the-job training were analyzed using non-parametric Wilcoxon comparative tests. From the pre-test and post-test data it was obtained the p-value of 0.007, so that 0.007<0.05 therefore reject H0. It shows that there are differences in the pre-test and post-test result of the learners.———————————————————————————–Tujuan penelitian ini adalah untuk mengetahui karakteristik dan efektivitas pembelajaran off job training untuk perbaikan hasil lasan pada boom excavator yang mengalami kerusakan dengan proses pengelasan GMAW pada peserta apprentice program group XXI Welder di PT Thiess. Penelitian ini menggunakan metode research and development. Pengumpulan data menggunakan metode observasi, wawancara, tes dan angket. Objek penelitian ini adalah peserta didik Apprentice Program bidang Welder group XXI PT Thiess dengan jumlah responden 10 orang. Teknik analisis data berupa statistik komparatif menggunakan uji non-parametrik, data yang ada dibandingkan berdasarkan hasil yang diperoleh dari instrumen penelitian. Hasil penelitian menunjukkan bahwa karakteristik pembelajaran off job training yaitu peserta terbatas dengan pembelajaran berupa group teaching dimana pesera didik bersifat aktif dengan metode simulasi. Efektifitas pembelajaran berdasarkan uji non-parametrik Wilcoxon menunjukkan bahwa nilai untuk data pre-test & post-test peserta didik p-value sebesar 0.007 sehingga 0,007 < 0,05 tolak H0 yang menyatakan bahwa ada perbedaan nilai pre-test dan post-test peserta didik pada pengembangan pembelajaran off job training perbaikan hasil lasan pada boom excavator.